3D sound with transaural audio beam system - Beh, Jia Wei. (2010)
In the world of sound, there are too many things to explore as there are many unknowns such as the human ear which is too complicated and complex to be fully understood. Thus many research and experiments lead to certain traits of the human ear. How a human ear perceives distance and direction is a mystery. That is why artificial human head models has been created in order to study the how humans actually hear the sound and perceive those distance and direction. Types of speakers also affect how realistic the 3D sounds are reproduced. This project aims to look into 3D sound reproduced using 2 speakers: ATC HATS directional speakers (ATC) and the Genelec conventional monitor speakers(GEN). Comparison between the 2 will be analyzed and evaluated.